Study of Steroidogenic Potential of Post-Thaw Biological Material of Mature Rats’ Testes - Pakhomov, A. V.; Bozhok, G. A.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2009)
Comparative study of steroidogenic potentials of biological material of testes of mature rats after cryopreservation was performed. Biological materials of testes as cryopreserved suspension of interstitial cells has higher ability to synthesize and secret sexual steroids if compared with testes fragments. Use of designed by us cryopreservation method for interstitial cell suspension (ICS) results in higher integrity of steroidogenic cells if compared with existing analogous regimens.